Methionine adenosyltransferases in liver health and diseases - Ramani, Komal (Liver Res, 2017)
Methionine adenosyltransferases (MATs) are essential for cell survival because they catalyze the biosynthesis of the biological methyl donor S-adenosylmethionine (SAMe) from methionine and adenosine triphosphate (ATP). Mammalian cells express two genes, MAT1A and MAT2A, which encode two MAT catalytic subunits, α1 and α2, respectively. The α1 subunit organizes into dimers (MATIII) or tetramers (MATI). The α2 subunit is found in the MATII isoform. A third gene MAT2B, encodes a regulatory subunit β, that regulates the activity of MATII by lowering the inhibition constant (K(i)) for SAMe and the Michaelis constant (K(m)) for methionine. MAT1A expressed mainly in hepatocytes maintains the differentiated state of these cells whereas MAT2A and MAT2B are expressed in non-parenchymal cells of the liver (hepatic stellate cells [HSCs] and Kupffer cells) and extrahepatic tissues. A switch from the liver-specific MAT1A to MAT2A has been observed during conditions of active liver growth and de-differentiation. Liver injury, fibrosis, and cancer are associated with MAT1A silencing and MAT2A/MAT2B induction. Even though both MAT1A and MAT2A are involved in SAMe biosynthesis, they exhibit distinct molecular interactions in liver cells. This review provides an update on MAT genes and their roles in liver pathologies.